2015
DOI: 10.18632/oncotarget.6272
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the pentose phosphate pathway by dichloroacetate unravels a missing link between aerobic glycolysis and cancer cell proliferation

Abstract: Glucose fermentation through glycolysis even in the presence of oxygen (Warburg effect) is a common feature of cancer cells increasingly considered as an enticing target in clinical development. This study aimed to analyze the link between metabolism, energy stores and proliferation rates in cancer cells. We found that cell proliferation, evaluated by DNA synthesis quantification, is correlated to glycolytic efficiency in six cancer cell lines as well as in isogenic cancer cell lines. To further investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 38 publications
2
43
0
3
Order By: Relevance
“…Al though stud ies on cell cul tures showed that mi to chon dr ial res pi ra tion is lim ited in sev eral can cer cell lines [262][263][264], in vivo data showed that mi to chon dr ial oxy gen con sump tion is not im paired in tu mors and that ox ida tive glu cose me tab o lism is re quired for tu mor growth [265]. The dis crep ancy be tween in vitro and in vivo ob ser va tions pleads for the use of spon ta neously aris ing tu mor mod els, which in te grate dri ver mu ta tions, the tu mor mi croen vi ron ment and the sur round ing 3D tis sue ar chi tec ture [253,266,267].…”
Section: Metabolic Differences Between In Vitro and In Vivo Models Ofmentioning
confidence: 99%
“…Al though stud ies on cell cul tures showed that mi to chon dr ial res pi ra tion is lim ited in sev eral can cer cell lines [262][263][264], in vivo data showed that mi to chon dr ial oxy gen con sump tion is not im paired in tu mors and that ox ida tive glu cose me tab o lism is re quired for tu mor growth [265]. The dis crep ancy be tween in vitro and in vivo ob ser va tions pleads for the use of spon ta neously aris ing tu mor mod els, which in te grate dri ver mu ta tions, the tu mor mi croen vi ron ment and the sur round ing 3D tis sue ar chi tec ture [253,266,267].…”
Section: Metabolic Differences Between In Vitro and In Vivo Models Ofmentioning
confidence: 99%
“…For example, in combination with certain platinum-based chemotherapies, DCA has been shown to enhance cytotoxicity in several solid tumor derived cell lines [61,62] and to reverse cisplatin resistance [63]. It is possible that DCA exacerbates the effects of these DNA cross-linking agents by reducing the biosynthesis of nucleotides necessary for DNA repair [64] or through other as-yet-undetermined metabolic effects.…”
Section: Catching Cancer In the Metabolic Crab Pot: Attempts Failurementioning
confidence: 99%
“…Otto Warburg identified in the 1920s the presence of a faster glycolytic flux in tumor cells [4], characterized by a high glucose uptake and increased lactate production even in the presence of oxygen. Despite a limited capacity for ATP production, aerobic glycolysis confers a major advantage to tumor cells by supporting proliferation and biomass production [3], [5], [6]. During decades, the loss of coupling between glycolysis and oxidative phosphorylation (OXPHOS) in tumor cells has been assigned to major mitochondrial dysfunctions [7].…”
Section: Introductionmentioning
confidence: 99%